2013
DOI: 10.1530/rep-12-0477
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy and efficiency of laser-assisted IVF in subfertile mutant mouse strains

Abstract: In the present report we studied the safety, efficacy and efficiency of using an infrared laser to facilitate IVF by assessing fertilization, development and birth rates after laser-zona drilling (LZD) in 30 subfertile genetically modified (GM) mouse lines. We determined that LZD increased the fertilization rate four to ten times that of regular IVF, thus facilitating the derivation of 26 of 30 (86.7%) GM mouse lines. Cryopreserved two-cell stage embryos derived by LZD-assisted IVF were recovered and developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…This finding has also been demonstrated in other studies, where mouse embryos generated through laser-assisted zona drilling developed to the blastocyst stage in vitro at a rate similar to conventional IVF [13], [17], [18], but had significantly lower birth rates [11], [12], [17], [34], [35]. Although not ruled out here, neither parthenogenic activation, nor polyspermy appear to be problems of LAIVF with mouse gametes [11], [13], [16][18].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding has also been demonstrated in other studies, where mouse embryos generated through laser-assisted zona drilling developed to the blastocyst stage in vitro at a rate similar to conventional IVF [13], [17], [18], but had significantly lower birth rates [11], [12], [17], [34], [35]. Although not ruled out here, neither parthenogenic activation, nor polyspermy appear to be problems of LAIVF with mouse gametes [11], [13], [16][18].…”
Section: Discussionsupporting
confidence: 88%
“…Whereas, LAIVF resulted in 42% two-cell embryos (n = 9,301/21,997), and was useful for obtaining live pups from 55 of 56 GM lines. Li et al found similarly low fertilization rates using fresh spermatozoa from subfertile GM C57BL/6 mice with conventional IVF (<15% two-cell embryos), while rates using LAIVF ranged from 25% to 85% two-cell embryos [12] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The thickness of the laser-perforated regions in the zona also impacts lentiviral gene delivery and embryo development (Li, Kinchen et al 2013). Larger laser-perforated regions result in higher number of blastocyst expressing the virally delivered gene.…”
Section: Resultsmentioning
confidence: 99%
“…Several approaches have been proposed to avoid the risk of laserinduced thermal damage to embryos. Among them are artificial shrinkage of oocytes (aimed at increasing the perivitelline space) during the IVF with laser-assisted zona drilling by adding sucrose to the culture medium [39][40][41]. Moreover, drilling location should be selected rather thoroughly at an area with no cells touching the zona pellucida.…”
Section: Discussionmentioning
confidence: 99%